The main factors determining the choice of self-presentation strategies in negotiations and business meetings - Mažeikienė, Aistė; Peleckienė, Valentina; Peleckis, Kęstutis (Business: Theory and Practice, 2010)
Factors determining the choice of self-presentation strategies are divided into three basic groups: individual personal factors, inter-individual factors, situational (of social environment) factors, which may be conditionally attributed to the outside factors. All these factors are closely interconnected and interacting not only during the presentation, but also when selecting goals and ways to achieve them. Thus, first of all it should be necessary to define stimuli affecting the person’s motivation for creating his own image in publicity and including not only the choice of a desirable image, but also a decision about what forms of behaviour are the most suitable for developing such an image, i.e. to select self-presentation strategies. It is also important to take into account some outside situational factors and the existing in the society social norms, which could influence the presentation planning and performance.